2006
DOI: 10.1213/01.ane.0000195581.74190.48
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Nitroglycerin Added to Lidocaine on Intravenous Regional Anesthesia

Abstract: We evaluated the analgesic effect of nitroglycerine (NTG) when added to lidocaine in IV regional anesthesia. Thirty patients undergoing hand surgery were randomly assigned to two groups. The control group (group C, n = 15) received a total dose of 40 mL with 3 mg/kg of lidocaine diluted with saline, and the NTG group (group NTG, n = 15) received an additional 200 mug NTG. Hemodynamic variables, tourniquet pain measured before and 1, 5, 10, 20, and 30 min after tourniquet inflation, and analgesic requirements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
(36 reference statements)
3
26
1
Order By: Relevance
“…Sen et al (11) reported shortened onset times for sensory and motor block, which was lower than what we found.…”
Section: Discussioncontrasting
confidence: 90%
“…Sen et al (11) reported shortened onset times for sensory and motor block, which was lower than what we found.…”
Section: Discussioncontrasting
confidence: 90%
“…[1,3] Different additives such as opioids, tramadol, nonsteroidal antiinflammatory drugs, dexmedetomidine, and muscle relaxant have been combined with LAs to improve block quality, prolong post-deflation analgesia and decrease tourniquet pain. [1,3,4] Sen and colleagues [5] showed that the addition of 200 µg nitroglycerine (NTG) to lidocaine for IVRA improves sensory and motor block, tourniquet pain and postoperative analgesia without side effects. They emphasized that more studies with different doses must be performed to determine a relevant conclusion before the routine use of NTG.…”
Section: Resultsmentioning
confidence: 99%
“…[5] They reported that postoperative VAS scores were significantly lower for the first 4 h postoperatively in Group NTG, in which 200 µg NTG was added to IVRA. The limitation of their study was using only one low dose of NTG (200 µg).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many additives can be used for prolongation of the duration of regional blockade. eg,dexamethasone, magnesium sulphate clonidine, nitroglycerin [5][6][7][8]. Tramadol hydrochloride is analgesic drug acting at central and peripheral m-opioid and monoaminergic receptors [9].…”
Section: Introductionmentioning
confidence: 99%